PENGARUH PPH 21 TERHADAP PENERIMAAN PADA KPP MAKASSAR SELATAN - Dellah Fadhilatunnisa; Amran Amran; Arsi Cahyani (Jurnal Riset Perpajakan: Amnesty, 2019)
This research was conducted to illustrate the extent of the influence of income tax acceptance of article 21 on tax revenues at Makassar's primary tax Service office. The method used in this research is a descriptive method with a quantitative approach. The research was conducted at Makassar South's primary tax office with methods of data collection in the form of document studies and field studies. Data analysis is expressed in the form of information that is developed with other data to obtain the clarity between variables so that the conclusion is withdrawn received or rejected hypothesis. The results showed that the results of the test that PPH article 21 have an effect on tax revenues at the primary tax office of the South Mkassar